2019
DOI: 10.3390/molecules24203756
|View full text |Cite
|
Sign up to set email alerts
|

The Fragment-Based Development of a Benzofuran Hit as a New Class of Escherichia coli DsbA Inhibitors

Abstract: A fragment-based drug discovery approach was taken to target the thiol-disulfide oxidoreductase enzyme DsbA from Escherichia coli (EcDsbA). This enzyme is critical for the correct folding of virulence factors in many pathogenic Gram-negative bacteria, and small molecule inhibitors can potentially be developed as anti-virulence compounds. Biophysical screening of a library of fragments identified several classes of fragments with affinity to EcDsbA. One hit with high mM affinity, 2-(6-bromobenzofuran-3-yl)aceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Secondly, DsbA is present in the periplasm, which is more accessible relative to cytoplasmic targets. Furthermore, all DsbA inhibitors described so far target the hydrophobic groove of DsbA [47] , [66] , [125] , [127] , [128] , [129] , [130] , which is not present in human thioredoxin or PDI. Therefore, despite DsbA belonging to the widespread thioredoxin superfamily, DsbA-tailored inhibitors are less likely to inhibit TRX-like proteins in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, DsbA is present in the periplasm, which is more accessible relative to cytoplasmic targets. Furthermore, all DsbA inhibitors described so far target the hydrophobic groove of DsbA [47] , [66] , [125] , [127] , [128] , [129] , [130] , which is not present in human thioredoxin or PDI. Therefore, despite DsbA belonging to the widespread thioredoxin superfamily, DsbA-tailored inhibitors are less likely to inhibit TRX-like proteins in humans.…”
Section: Discussionmentioning
confidence: 99%
“…MS and X-ray Sijbesma et al, 2019 The RNA-dependent RNA polymerase X-ray Riccio et al, 2019 Apical membrane antigen 1 PRE, NMR Akter et al, 2019 Glyoxalase 1 Computational approach Perez et al, 2019 Focal Adhesion Kinase SPR and NMR Alvarado et al, 2019 E. coli DsbA NMR/X-ray Duncan et al, 2019 PDEδ-RAS (PPI) STD, CMPG-NMR Chen et al, 2019 *This table lists some studies using FBDD. Only a few studies published in 2019 were list for elucidating the application of FBDD to multiple targets.…”
Section: Growing Of Fragment Hitsmentioning
confidence: 99%
“…Previous studies have identified small-molecule inhibitors, phenylthiazole, benzofuran, and pyridazinone derivatives, against the DsbA/DsbB system in E. coli . Pyridazinone-based compounds [ 161 , 163 , 165 , 169 ] bound to Ec DsbB at the quinone-binding site between the first two transmembrane segments, competing with quinone, or to a segment of the second periplasmic loop that interacts with Ec DsbA [ 164 , 271 ]. Phenylthiazole and benzofuran-based compounds bound to the hydrophobic groove of Ec DsbA, which is required for interaction with Ec DsbB [ 163 , 169 ].…”
Section: Gonococcal Virulence Factors As Targets For Inhibitor Desmentioning
confidence: 99%
“…Pyridazinone-based compounds [ 161 , 163 , 165 , 169 ] bound to Ec DsbB at the quinone-binding site between the first two transmembrane segments, competing with quinone, or to a segment of the second periplasmic loop that interacts with Ec DsbA [ 164 , 271 ]. Phenylthiazole and benzofuran-based compounds bound to the hydrophobic groove of Ec DsbA, which is required for interaction with Ec DsbB [ 163 , 169 ]. Phenylalanine and tyrosine-based phenylthiazole derivatives were also found to selectively inhibit Ec DsbA in in vitro assays, with reduced motility in soft agar and no effect on growth in liquid media [ 163 ].…”
Section: Gonococcal Virulence Factors As Targets For Inhibitor Desmentioning
confidence: 99%